Fetal Surface Placental Hematomas: the Clue in the Diagnosis of a Bleeding Dyscrasia - Mansilla, Luis P.; Martin, Dibe (Puerto Rico Health Sciences Journal, 2013)
Von Willebrand disease (vWD) is the most common inherited bleeding disorder in humans, occurring in about 1% of women and caused by a deficiency or abnormality in the von Willebrand factor (vWF). There are different types of vWD. Type I comprises approximately 80% of the cases, its inheritance is autosomal dominant. Women with vWD have a 10-fold risk of having antepartum bleeding when compared to the general population. We report a case of von Willebrand disease diagnosed due to findings on a routine ultrasound evaluation.